Clinical profile of diabetes mellitus in tuberculosis. Issue 1 (28th August 2015) - Ogbera, Anthonia Okeoghene; Kapur, Anil; Abdur-Razzaq, Hussein; Harries, Anthony D; Ramaiya, Kaushik; Adeleye, Olufunmilayo; Kuku, Sonny
Abstract : Objective: The objective is to document the clinical profile of diabetes mellitus (DM) in tuberculosis (TB). Type of study: This was a descriptive observational study. Methods: A total of 4000 persons aged above 12 years with a confirmed diagnosis of TB and on treatment were recruited. The study subjects were screened for DM and diagnoses were made on the basis of the WHO criteria. Clinical parameters were compared between persons with DM and those without DM. Results: Mean age was higher in patients with TB and DM than in persons without DM, and this difference was statistically significant (40.9 vs 39.6 years, p=0.0002). DM/TB comorbidity was noted in 480 persons and these made up 12.3% of the study population. Some clinical features of patients with TB who had DM included a positive family history of DM, a history of hypertension, and central obesity. Conclusions: Given the substantial burden of DM and TB comorbidity, we recommend that patients with TB be screened routinely for DM. However, further research is needed to clarify the risk factors for the occurrence of DM in TB.